2010
DOI: 10.1021/la1015109
|View full text |Cite
|
Sign up to set email alerts
|

Photoswitching Behavior of Azobenzene-Containing Alkanethiol Self-Assembled Monolayers on Au Surfaces

Abstract: The photoisomerization of self-assembled monolayers of azobenzene-containing alkanethiols, as well as of mixed monolayers of these substances with n-alkanethiol spacer molecules on Au surfaces, was studied by photoelectrochemical measurements and surface plasmon resonance spectroscopy. A strong dependence on the molecular structure of the adsorbates was found, specifically on the linker between the azobenzene moiety and the alkanethiol: while molecules with an amide group were photoinactive, those with an ethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
81
3
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(91 citation statements)
references
References 80 publications
6
81
3
1
Order By: Relevance
“…[7][8][9][10][11][12] Unfortunately, such systems come with a substantial drawback: The photo-isomerization rate is drastically suppressed due to steric hindrance or excitonic coupling. 13,14 A number of experimental strategies have been suggested to overcome this problem, such as replacing the aliphatic linker by an aromatic one 15 or even bulkier groups, [16][17][18] or diluting the azobenzene moieties in densely-packed alkanethiolate SAMs. 14,[19][20][21][22] From a theoretical viewpoint the issue of hindered photo-isomerization in densely-packed azobenzenefunctionalized SAMs has been addressed by a few works, mainly focused on the excitonic coupling between the chromophores, 23,24 as well as on the effects of a metal substrate.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12] Unfortunately, such systems come with a substantial drawback: The photo-isomerization rate is drastically suppressed due to steric hindrance or excitonic coupling. 13,14 A number of experimental strategies have been suggested to overcome this problem, such as replacing the aliphatic linker by an aromatic one 15 or even bulkier groups, [16][17][18] or diluting the azobenzene moieties in densely-packed alkanethiolate SAMs. 14,[19][20][21][22] From a theoretical viewpoint the issue of hindered photo-isomerization in densely-packed azobenzenefunctionalized SAMs has been addressed by a few works, mainly focused on the excitonic coupling between the chromophores, 23,24 as well as on the effects of a metal substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies employed rather indirect methods for investigating the photoisomerization in these photochromic SAMs, such as surface plasmon resonance spectroscopy (SPR) 11,[30][31][32] or electrochemical techniques 31,33 . Here, a signal is measured, which is coupled in a complex way to the different optical or chemical properties of the trans and cis state.…”
Section: Introductionmentioning
confidence: 99%
“…Recent STM data have shown that mixed SAMs of C4 and the molecular switch 3-(4-(4-hexyl-phenylazo)-phenoxy)-propane-1-thiolate exhibit a similar superstructure [15]. Our experimental results are in qualitative agreement with 2PPE spectra of in situ prepared hexanethiolate [CH 3 -(CH 2 ) nÀ1 -S-, n = 6] SAMs on Au (111)-in the following referred to as C6/Au (111) [11].…”
Section: Introductionmentioning
confidence: 99%